Comparison of the local pulmonary distribution of nanoparticles administered intratracheally to rats via gavage needle or microsprayer delivery devices. Issue 4 (6th October 2016) - Zhang, Guihua; Shinohara, Naohide; Oshima, Yutaka; Kobayashi, Toshio; Imatanaka, Nobuya; Kawaguchi, Kenji; Gamo, Masashi
Abstract: Intratracheal administration methods are used to conduct toxicological assessments of inhaled nanoparticles (NPs), and gavage needles or microsprayers are common intratracheal delivery devices. The NP suspension is delivered in a liquid state via gavage needle and as a liquid aerosol via microsprayer. The differences in local pulmonary NP distribution (called the microdistribution) arising from the different states of the NP suspension cause differential pulmonary responses; however, this has yet to be investigated. Herein, using microbeam X‐ray fluorescence microscopy, we quantitatively evaluated the TiO2 pulmonary microdistribution (per mesh: 100 μm × 100 μm) in lung sections from rats administered an intratracheal dose of TiO2 NPs (6 mg kg −1 ) via gavage needle or microsprayer. The results revealed that: (i) using a microsprayer appears to reduce the variations in TiO2 content (ng mesh −1 ) among rats (e.g., coefficients of variation, n = 3, microsprayer vs gavage needle: 13% vs 30%, for the entire lungs); (ii) TiO2 appears to be deposited less in the right middle lobes than in the rest of the lung lobes, irrespective of the chosen intratracheal delivery device; and (iii) similar TiO2 contents (ng mesh −1 ) and frequencies are deposited in the lung lobes of rats administered TiO2 NPs via gavage needle or microsprayer. This suggests that the physical state of the administered NP suspension does not markedly alter TiO2 pulmonary microdistribution. The results of this investigation are important for the standardization of intratracheal administration methods. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Nanoparticle suspensions can be delivered in liquid state, via gavage needle or as liquid aerosol, using a microsprayer as the intratracheal delivery device. We quantitatively evaluated TiO2 pulmonary microdistribution (per mesh: 100 μm × 100 μm) in lung sections from rats administered an intratracheal dose of TiO2 nanoparticles (6 mg kg −1 ) via gavage needle or microsprayer, using microbeam X‐ray fluorescence microscopy. The evidence suggests that the state of administered nanoparticle suspension does not markedly alter TiO2 pulmonary microdistribution.